Scaling biocultural initiatives can support nature, food, and culture from summit to sea - Jade M. S. Delevaux; Kostantinos A. Stamoulis; Natalie Kurashima; Clay Trauernicht; Tamara Ticktin; Nathan DeMaagd; Lida Teneva; Gina McGuire; Zoe Hastings Silao; Leah L. Bremer (npj Ocean Sustainability)
Abstract Biocultural nature-based solutions provide many social, cultural, and ecological benefits. Yet, there has been little research on related land-sea societal benefits, hindering our ability to finance and scale these solutions. To help fill this gap, we evaluate the land-sea benefits of scaling biocultural restoration initiatives in Hawaiʻi, including multi-strata agroforestry and high-elevation silvopasture combined with native forest protection. We innovated and integrated a blue food production model into a land-sea modeling framework to illustrate the societal benefits of biocultural restoration efforts. Our results show that agroforestry transitions add value to forest protection by increasing sediment retention (30%) and nearshore fisheries production (10%) across all islands, while also supporting goals of biodiversity conservation, food production, and cultural connection to place. We demonstrate that the biocultural restoration of forests are nature-based solutions that provide a triple win for nature, people, and culture, and are critical to social-ecological resilience.